Role of Positron Emission Tomography for the Monitoring of Response to Therapy in Breast Cancer. (5th January 2015) - Humbert, Olivier; Cochet, Alexandre; Coudert, Bruno; Berriolo-Riedinger, Alina; Kanoun, Salim; Brunotte, François; Fumoleau, Pierre
Abstract: This review considers the potential utility of positron emission tomography (PET) tracers in the setting of response monitoring in breast cancer, with a special emphasis on glucose metabolic changes assessed with 18 F-fluorodeoxyglucose (FDG). In the neoadjuvant setting of breast cancer, the metabolic response can predict the final complete pathologic response after the first cycles of chemotherapy. Because tumor metabolic behavior highly depends on cancer subtype, studies are ongoing to define the optimal metabolic criteria of tumor response in each subtype. The recent multicentric randomized AVATAXHER trial has suggested, in the human epidermal growth factor 2-positive subtype, a clinical benefit of early tailoring the neoadjuvant treatment in women with poor metabolic response after the first course of treatment. In the bone-dominant metastatic setting, there is increasing clinical evidence that FDG-PET/computed tomography (CT) is the most accurate imaging modality for assessment of the tumor response to treatment when both metabolic information and morphologic information are considered. Nevertheless, there is a need to define standardized metabolic criteria of response, including the heterogeneity of response among metastases, and to evaluate the costs and health outcome of FDG-PET/CT compared with conventional imaging. New non-FDG radiotracers highlighting specific molecular hallmarks of breast cancer cells have recently emerged in preclinical and clinical studies. These biomarkers can take into account the heterogeneity of tumor biology in metastatic lesions. They may provide valuable clinical information for physicians to select and monitor the effectiveness of novel therapeutics targeting the same molecular pathways of breast tumor. Abstract : This review considers the potential utility of positron emission tomography (PET) tracers in the setting of response monitoring in breast cancer, with a special emphasis on glucose metabolic changes assessed with 18 F-fluorodeoxyglucose. It discusses the different PET timing and metabolic criteria to define response that have been evaluated in previous studies. The development of new radiotracers of specific molecular pathways of breast cancer cells is also a challenging and promising research area.